Insidentaloma Tiroid - Christilia Oktaviani; Erwin Affandi Soeriadi; Trias Nugrahadi (Jurnal Health Sains, 2022)
Thyroid cancer is the most common type of endocrine cancer. Thyroid cancer begins with the formation of nodule in the thyroid gland. Thyroid nodule is frequently discovered incidentally during physical examination and by anatomic or functional imaging (incidentaloma). The aim of thyroid scintigraphy in the evaluation of thyroid nodule is to determine the functional status of the thyroid nodule which will impact its management options. The risk of malignancy is low in a functional thyroid nodule. A 65-year-old woman was admitted with complaints of shortness of breath, difficulty in swallowing, and low voice. On physical examination, a nodule was found in the inferior part of the left thyroid gland with a size of approximately 4 cm. Multiple lymphadenopathies was also palpable in the bilateral jugular and supraclavicular areas. Ultrasound imaging showed an image of thyroiditis, then the thyroid scintigraphy and SPECT/CT was done using radiopharmaceutical Tc-99m Pertechnetate which showed an image of a functional nodule that was pressing against the trachea. Histopathological examination using fine needle aspiration biopsy with ultrasound guidance yielded papillary thyroid carcinoma. The risk of malignancy in functional nodule is very low but we should aware of malignancy if the assessment of risk stratification is high. Integrated planar and SPECT/CT of thyroid scintigraphy has an incremental value to predict thyroid cancer in patient who have a high risk of malignancy.